Perspective on career assessment tools for evaluating students with specific learning disabilities - Eseadi, Chiedu; Diale, Boitumelo M (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2023)
Purpose - The purpose of this research was to examine career assessment tools for evaluating students with specific learning disabilities (SLDs).Method - The paper adopted a narrative literature review of research papers connected to assessment tools for SLD students. Among the databases looked at were Pubmed, Google Scholar, Index Copernicus, and PsycINFO.Result - The results emphasize the need for assessment tools to take certain domains of difficulty into consideration when evaluating the interests and skills of students with SLDs and profiling the learning characteristics linked with the individual learning impairment also offers useful information for job preparation.Implication – Students with SLDs typically have limited career options so it would be crucial to consider career evaluation as part of the career planning and transitioning process for this group.Originality - This research reinforces the significance of employing career assessment tools for the evaluation of persons with SLDs in the process of career transition.***Tujuan - Tujuan dari penelitian ini adalah untuk menguji alat asesmen karir untuk mengevaluasi siswa dengan ketidakmampuan belajar spesifik (SLD).Metode - Makalah ini menggunakan tinjauan literatur naratif terhadap makalah penelitian yang berhubungan dengan alat penilaian untuk siswa SLD. Di antara basis data yang ditinjau adalah Pubmed, Google Scholar, Index Copernicus, dan PsycINFO.Hasil - Hasil penelitian menekankan perlunya alat asesmen untuk mempertimbangkan domain kesulitan tertentu ketika mengevaluasi minat dan keterampilan siswa dengan SLD dan membuat profil karakteristik pembelajaran yang terkait dengan gangguan belajar individu juga menawarkan informasi yang berguna untuk persiapan kerja.Implikasi - Siswa dengan SLD biasanya memiliki pilihan karir yang terbatas, sehingga akan sangat penting untuk mempertimbangkan evaluasi karir sebagai bagian dari perencanaan karir dan proses transisi untuk kelompok ini.Keaslian - Penelitian ini memperkuat pentingnya penggunaan alat asesmen karir untuk mengevaluasi siswa dengan SLD dalam proses transisi karir.